Epoxymicranthols A—N, 5, 9‐Epoxygrayanane Diterpenoids as Potent Analgesics from Rhododendron micranthum. Issue 7 (4th June 2021) - Jin, Pengfei; Yuan, Xinghua; Ma, Xiaomin; Zheng, Guijuan; Wang, Ru; Sun, Na; Yao, Guangmin
Main observation and conclusion: Fifteen 5, 9‐epoxygrayanane diterpenoids (1—15) including fourteen new ones, epoxymicranthols A—N (1—14), were isolated from the leaves extract of Rhododendron micranthum . Their structures were elucidated via extensive spectroscopic methods and 13 C NMR‐DP4+ analysis, and the absolute configurations of 1, 3—10, 14, and 15 were confirmed by single‐crystal X‐ray diffraction analysis. Epoxymicranthols A—C (1—3) represent the first examples of 14α‐hydroxygrayanane diterpenoids, and epoxymicranthols C—F (3—6) are the first examples of 10β‐hydroxy‐5, 9‐epoxygrayanane diterpenoids. Meanwhile, epoxymicranthols K (11) and N (14) represent the first examples of 13‐hydroxy‐5, 9‐epoxygrayanane and 5, 9‐epoxygrayan‐3‐one diterpenoids, respectively. All the diterpenoids (1—15) were assayed for their analgesic activities, and all of them exhibited significant analgesic activities at a dose of 5.0 mg/kg. Among them, compounds 2, 7, 8, and 10 also exhibited significant analgesic activities even at lower doses of 1.0 and 0.2 mg/kg. More importantly, epoxymicranthol G (7) still expressed potent analgesic activity at a lower dose of 0.04 mg/kg. A preliminary structure‐activity relationship for the analgesic effects of 5, 9‐epoxygrayanane diterpenoids 1—15 is discussed. These results not only enlarged the structural diversity of 5, 9‐epoxygrayanane diterpenoids, but also provided a basis to develop novel potent analgesics. Abstract : Fifteen 5, 9‐epoxygrayanane diterpenoids including fourteen new ones were isolated from the leaves of Rhododendron micranthum . Epoxymicranthols A—C (1—3) represent the first examples of 14α‐hydroxygrayanane diterpenoids. Epoxymicranthols C—F (3—6) are the first examples of 10β‐hydroxy‐5, 9‐epoxygrayanane diterpenoids. All the isolates exhibited significant analgesic activities. A preliminary structure‐activity relationship is discussed.